2016
DOI: 10.1186/s12944-016-0297-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipids profile among ART-naïve HIV infected patients and men who have sex with men in China: a case control study

Abstract: BackgroundDyslipidemia is commonly seen in human immunodeficiency virus (HIV) infected patients. Understanding the risk factors of abnormal lipid profiles is urgent for proposing targeted approaches to prevention. Our objective was to assess the incidence and associated factors of abnormal lipid profiles and atherogenic index of plasma (AIP) among antiretroviral therapy (ART) naïve men who have sex with men (MSM) acute HIV infection (AHI) and chronic HIV infection (CHI) patients in China.MethodsWe compared lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Several studies from the Asian region showed that dyslipidaemia was less prevalent in patients who were first presented with HIV compared to their HIV negative counterparts [ 19 , 20 ]. Cholesterol levels were on average lower in HIV positive patients [ 19 - 22 ], whereas findings were inconsistent regarding triglyceride levels [ 19 - 21 ].…”
Section: Risk Factors Of Cardiovascular Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…Several studies from the Asian region showed that dyslipidaemia was less prevalent in patients who were first presented with HIV compared to their HIV negative counterparts [ 19 , 20 ]. Cholesterol levels were on average lower in HIV positive patients [ 19 - 22 ], whereas findings were inconsistent regarding triglyceride levels [ 19 - 21 ].…”
Section: Risk Factors Of Cardiovascular Diseasementioning
confidence: 99%
“…In Malaysia, dyslipidaemia was reported in 82% of patients on ART [ 23 ]. Other evidence from the Asian region indicated abnormal levels of triglycerides, TC, LDL and HDL in 7-39%, 3-8%, 2-17% and 19-86% of ART naïve patients, respectively [ 19 - 22 , 24 - 26 ], compared to 39-54%, 26-54%, 22-48% and 14-68% of ART experienced patients, respectively [ 15 , 19 , 20 , 23 - 27 ].…”
Section: Risk Factors Of Cardiovascular Diseasementioning
confidence: 99%
See 3 more Smart Citations